Power in the 21st century : China's soft power in Latin America and its global rise. - Ball, Matthew R. (My University, 2013)
The People's Republic of China pursues soft power in the western hemisphere to support its national interest. Joseph Nye's concept of soft power lacks the necessary detail to be considered mature theory, focuses far too heavily on soft power resource supply, and fails to account for state utility of soft power. As a result, Nye is wrongfully dismissive of China's soft power presence and capabilities. As the case of Latin America demonstrates, China's "utility of scale" soft power approach enables China to exact favorable policy outcomes that serve the national interest by driving its continued economic growth. Chinese soft power in Latin America has peripheral strategic implications, but does not directly impede on the long held Monroe Doctrine; rather, it very deliberately respects it. China's soft power reinforces a key component of PRC grand strategy called "hemispheric hedging," which provides a conceptual construct for understanding comprehensive Chinese smart power.
Keywords: Nye, Joseph S.; International relations; China; Latin America; Nye; Soft Power